Risk factors and management of medical disputes: An analysis of preliminary appraisal reports - Chu-Tzu Chang; Yung-Po Liaw (PLoS ONE, 2025)
Background Medical disputes represent a growing challenge in healthcare, with implications for patient safety, legal liability, and institutional trust. Identifying contributing factors and risk patterns is essential for developing effective prevention strategies. Methods We analyzed 70 preliminary medical dispute appraisal reports from Chung Shan Medical University Hospital (CSMUH), commissioned by Taiwan’s Ministry of Health and Welfare between 2017 and 2023. Descriptive statistics and logistic regression were used to examine demographic characteristics, institutional and specialty distributions, and associations between duty violations and malpractice determinations. Results Most physician respondents were male (76.92%), while 56.16% of patients were female. Disputes were most frequently associated with medical centers (35.70%) and clinics (32.90%). In terms of specialty classification, surgical departments accounted for 55.29% of the specialties involved, including obstetrics and gynecology, orthopedics, and neurosurgery. Non-surgical departments accounted for 44.71%, including neurology, emergency medicine, and internal medicine. Violations of standard medical practice, incomplete documentation, and inadequate preoperative assessment were significantly associated with malpractice findings. Notably, inadequate preoperative assessment had an odds ratio (OR) of 39.74 (95% CI: 3.33–474.98, P = 0.0036), and disclosure failures had an OR of 12.75 (95% CI: 1.91–84.95, P = 0.0085). Conclusions Duty violations related to clinical decision-making and informed consent significantly increase the likelihood of malpractice determinations. Targeted interventions in high-risk specialties and outpatient settings may improve legal defensibility and reduce preventable disputes.